Perancangan Sistem Informasi Pemasaran (E-Commerce) PT. Jogja Kelapa Mas Berbasis Web - Zulkifli Zulkifli (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2016)
The Internet is a global computer network that connects the world in a network. Evolution happens on the Internet is one of the most interesting phenomena in technological advancements happening no. One aspect that is arguably the principal in this evolution is the emergence of Electronic Commerce (E-commerce) in the business environment. Sale and purchase transactions so that can be done without having to come to the seller. PT. Jogja Kelapa Mas is a company engaged in the Supplier of coconut sugar, virgin coconut oil and Fresh coconut. Product marketing and sales process is still largely done manually and marketing processesis still minimal use of technology, that only use telephone, email, social media, advertising, and advertising on the website advertising space provider so the company is not very well known people. So to overcome this system is designed marketing or sales (e-commerce) PT. Jogja Kelapa mas based website that consists of 12 pages which display form 7 form the product information page, informing about coconut sugar, original coconut oill, and fresh coconut, 2 pages of company information that informs the company profile and contact the company, 2 page admin form as a page to enter or edit the information on web pages as well asview a page of customer orders, and a customer order form page that appears when users access the system, so that the product sales process can be done easily and is a place to publish product companies that can be seen by the customer with the utmost of various villages, cities, and even countries.